Experimental detection using cyclostationary feature detectors for cognitive radios - Zolfaghari, M.; Fanan, A.; Mehdawi, M.; Riley, N. G.; Ammar, M. (Telecommunications forum Telfor (TELFOR), 2014 22nd, 2014)
© 2014 IEEE. Signal detection is widely used in many applications. Some examples include Cognitive Radio (CR) and military intelligence. Without guaranteed signal detection, a CR cannot reliably perform its role. Spectrum sensing is currently one of the most challenging problems in cognitive radio design because of various factors such as multi-path fading and signal to noise ratio (SNR). In this paper, we particularly focus on the detection method based on cyclostationary feature detectors (CFD) estimation. The advantage of CFD is its relative robustness against noise uncertainty compared with energy detection methods. The experimental result present in this paper show that the cyclostationary feature-based detection can be robust compared to energy-based technique for low SNR levels.
Keywords: Cognitive radio; Cyclostationary detectors; Power spectral density; Spectral correlation function 2014